2021
DOI: 10.3390/pharmaceutics13030351
|View full text |Cite
|
Sign up to set email alerts
|

Optimising an Infusion Protocol Containing Cefepime to Limit Particulate Load to Newborns in a Neonatal Intensive Care Unit

Abstract: Background: In neonatal intensive care units (NICUs), the simultaneous administration of drugs requires complex infusion methods. Such practices can increase the risk of drug incompatibilities resulting in the formation of a particulate load with possible clinical consequences. Methods: This paper evaluates strategies to reduce the particulate load of a protocol commonly used in NICUs with a potential medical incompatibility (vancomycin/cefepime combination). The protocol was reproduced in the laboratory and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…In vitro studies have clearly shown the impact of filters on the retention of particles present in infused solutions [ 50 , 51 ]. In the present in vitro study, no precipitate was observed downstream of the in-line filter.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have clearly shown the impact of filters on the retention of particles present in infused solutions [ 50 , 51 ]. In the present in vitro study, no precipitate was observed downstream of the in-line filter.…”
Section: Discussionmentioning
confidence: 99%